Democracy, Governance and Legitimacy in Zimbabwe since the November 2017 Military Coup - Aaron Rwodzi (Cadernos de Estudos Africanos)
This article focuses on the democracy and legitimacy debates in Zimbabwe after the ouster of Robert Mugabe from power by his erstwhile ally, Emmerson Mnangagwa, in November 2017. President Mnangagwa popularized the terms “Second Republic” and “New Dispensation” to show that his regime differed from Mugabe’s in terms of governance style. The position of this article is that Mnangagwa’s regime could not abandon the system established under the reign of Mugabe. Instead, it argues that the Second Republic reflects continuities of the Mugabe era being transposed into a quasi-military edifice whose commandist approaches denigrate cries for democracy and transparency. This qualitative research draws on data from interviews with political elites in the opposition and ruling parties as well as secondary sources.